TRADISI LUKAH GILO MASYARAKAT BONAI KABUPATEN ROKAN HULU:PEMBELAJARAN ANALISIS SEMIOTIKA - Misra Nofrita; Hermawan Hermawan (STKIP ROKANIA, 2018)
This study aims to describe the oral tradition of the Luka Gilo Bonai community which was analyzed in terms of semiotics. This study uses a qualitative approach. The method used is descriptive analysis. The data source is the Bonai community. The data in this study are in the form of tools, words, sentences, and oral traditions of the Bonai community. The results of this study are in the form of semiotic meanings contained in ritual performances if gilo socially has the meaning as maintaining the interrelated social integration fabric. Another meaning of ritual lukah gilo is an expression of the fabric of communication between the human world and the unseen world